Genetic variation in inflammatory and bone turnover pathways and risk of osteolytic responses to prosthetic materials. Issue 2 (16th November 2014) - MacInnes, Scott J.; Vescovo, Elena Del; Kiss‐Toth, Endre; Ollier, William E.R.; Kay, Peter R.; Gordon, Andrew; Greenfield, Edward M.; Wilkinson, Mark J.
ABSTRACT Wear particle‐induced inflammatory bone loss (osteolysis) is the leading cause of total hip arthroplasty (THA) failure. Individual susceptibility to osteolysis is modulated by genetic variation. In this 2‐stage case‐control association study we examined whether variation within candidate genes in inflammatory and bone turnover signaling pathways associates with susceptibility to osteolysis and time to prosthesis failure. We examined two cohorts, comprising 758 (347 male) Caucasian subjects who had undergone THA with a metal on polyethylene bearing couple; 315 of whom had developed osteolysis. Key genes within inflammatory, bone resorption, and bone formation pathways were screened for common variants by pairwise‐SNP tagging using a 2‐stage association analysis approach. In the discovery cohort four SNPs within RANK, and one each within KREMEN2, OPG, SFRP1, and TIRAP (p < 0.05) were associated with osteolysis susceptibility. Two SNPs within LRP6, and one each within LRP5, NOD2, SOST, SQSTM1, TIRAP, and TRAM associated with time to implant failure (p < 0.05). Meta‐analysis of the two cohorts identified four SNPs within RANK, and one each within KREMEN2, OPG, SFRP1, and TIRAP associated with osteolysis susceptibility (p < 0.05). Genetic variation within inflammatory signaling and bone turnover pathways may play a role in susceptibility to osteolysis. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:193–198, 2015.